Role of toll-like receptors 2 and 4, and the receptor for advanced glycation end products in high-mobility group box 1-induced inflammation in vivo - van Zoelen, Marieke A D; Yang, Huan; Florquin, Sandrine; Meijers, Joost C M; Akira, Shizuo; Arnold, Bernd; Nawroth, Peter P; Bierhaus, Angelika; Tracey, Kevin J; van der Poll, Tom (Shock (Augusta, Ga.), 2009)
High-mobility group box 1 (HMGB-1) has been reported as a "late" proinflammatory mediator in sepsis. In vitro data have shown that HMGB-1 can induce activation of intracellular signaling pathways via interaction with at least three pattern recognition receptors: Toll-like receptor (TLR) 2, TLR-4, and the receptor for advanced glycation end products (RAGE). The objective of this study was to investigate the role of these receptors in the in vivo response to HMGB-1. Therefore, we first performed a time-series experiment with wild-type (Wt) mice. High-mobility group box 1 induced time-dependent elevations of TNF-alpha, IL-6, monocyte chemoattractant protein 1, and thrombin-antithrombin complex levels in peritoneal lavage fluid and plasma. This inflammatory reaction was accompanied by a prominent and sustained rise in neutrophil counts in the peritoneal cavity. We next administered HMGB-1 to Wt, TLR-2, TLR-4, and RAGE mice. All genotypes showed similar plasma levels of TNF-alpha, IL-6, IL-10, and thrombin-antithrombin complex at 2 h after intraperitoneal injection of HMGB-1. Compared with Wt mice, both TLR-4 and RAGE mice displayed lower TNF-alpha and IL-6 concentrations and lower neutrophil numbers in their peritoneal lavage fluid. In contrast, TLR-2 mice showed increased levels of TNF-alpha and IL-6 in their peritoneal cavity relative to Wt mice. These data indicate that HMGB-1 induces release of cytokines, activation of coagulation, and neutrophil recruitment in vivo via a mechanism that at least in part depends on TLR-4 and RAGE.